Racehorse in the Rain - Baglio, Ben M.; Nang Chan Yeema (New York, USA Scholastic Inc., 2004)
At Animal Ark, Mandy Hope helps her parents treat animals of all shapes and sizes. Even outside the clinic, Mandy can't resist aiding any animal in need-and sometimes even ghostly animals need her help.
Keywords: Story Collection